FGF2 supports NANOG expression via pyruvate dehydrogenase–dependent histone acetylation under low oxygen conditions - Fojtík, Petr; Senfluk, Martin; Holomkova, Katerina; Salykin, Anton; Gregorova, Jana; Smak, Pavel; Pes, Ondrej; Raska, Jan; Beckerova, Deborah; Stetkova, Monika; Skladal, Petr; Sedlackova, Miroslava; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe safe and effective application of human pluripotent stem cells (hPSCs) in research and regenerative medicine requires precise control over pluripotency and cell fate. Pluripotency is characterized by high histone acetylation and aerobic glycolysis, while differentiation involves metabolic remodeling and reduced acetylation. Pyruvate dehydrogenase (PDH) links these processes by converting glycolytic pyruvate into acetyl coenzyme A (Ac-CoA), the key substrate for histone acetylation.MethodsWe investigated how PDH activity regulates histone acetylation and pluripotency maintenance under physiologically relevant oxygen levels (5% and 21% O₂). PDH contribution to histone acetylation was assessed using a specific PDH inhibitor, followed by rescue experiments with acetyl-CoA precursors. hPSCs were exposed to variations in FGF2 signaling and reactive oxygen species (ROS) using H₂O₂ treatment to evaluate redox-dependent modulation of PDH and downstream effects on pluripotency factors. Protein levels and post-translational modifications were analyzed by Western blotting and quantitative PCR, relative metabolite concentrations by LC–MS, and ROS levels by fluorescence microscopy.ResultsActive PDH promoted global histone H3 acetylation and upregulated the expression of the pluripotency factor NANOG, specifically under 5% O₂. Mechanistic analysis revealed a novel FGF2–MEK1/2–ERK1/2–ROS signaling axis that regulates PDH activity through redox-sensitive mechanisms. This regulatory pathway was oxygen-dependent and absent under atmospheric oxygen levels (21% O₂).DiscussionThese findings identify PDH as a redox-sensitive metabolic switch connecting cellular metabolism with the epigenetic control of pluripotency by modulating Ac-CoA availability.ConclusionOur study highlights the importance of oxygen tension, ROS homeostasis, and growth factor signaling in shaping the metabolic–epigenetic landscape of hPSCs, with implications for optimizing stem cell culture and differentiation protocols.